Strategic Manoeuvres and Impression Management: Communication Approaches in the Case of a Crisis Event - O'Connell, B.; De Lange, Paul; Stoner, G.; Sangster, A. (Routledge Taylor & Francis Group, 2016)
This historical study examines the actions of the Australian former asbestos company, James Hardie, when faced with a potentially ruinous corporate scandal between 2001 and 2007. The company became vilified as public awareness grew of the damage to public health its use of asbestos had caused. In response, it set-up a knowingly underfunded compensation fund supported by a strategy of misinformation and denial. Its actions are analysed using Oliver’s typology of strategic responses and theories of crisis management and crisis communications, providing insights into the company’s motivations for adopting strategies that took it to the brink of financial collapse.